ANALISIS SEMIOTIKA PUISI BAHASA MELAYU MANADO œCAP TIKUS BLUES KARYA FREDY WOWOR - Palit, Anatje Tineke; Humena, Stefanie; Pua, Christo Rilco; Karouw, Stella (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2023)
This research is a study of the science of sign or semiotic, which aims to reveal the cultural meaning of Manado-Malay speaking community. The sign discussed is the sign found in Manado-Malay poem entitled